Analisis Pengaruh Teknik Digital dalam Interaksi Sosial dalam Era Digital - Muhammad Ariel Saputra; Aura Rahellita Putri; Qorifisya Rachely Hamsyah; Muhammad Faiz Ardiansyah; Muhammad Habib Zakaria; Denny Oktavina Radianto (LPPM IAI Nasional Laa Roiba Bogor, 2023)
This study aims to analyze the influence of digital techniques on social interaction in the digital era. In an era where information and communication technology is increasingly dominating everyday life, the development of digital techniques has had a significant impact on the way we interact and relate socially. First, this study will discuss the influence of digital techniques on interpersonal communication. Digital technology has changed the way we communicate with others. The use of social media, instant messaging applications and other digital platforms has facilitated faster, easier and more practical communication. However, research also shows that the use of digital technology can reduce the quality of face-to-face social interactions and result in social isolation. Furthermore, this study will explore the influence of digital techniques on patterns of social relations. The emergence of social media has changed the way we build and maintain social relationships. In some cases, social media can expand our social network and allow us to connect with people from various backgrounds. This study aims to provide a more comprehensive understanding of the implications of using digital techniques in social interaction. By analyzing the influence of digital techniques on interpersonal communication, patterns of social relations, and social interactions in the public sphere, this research can provide insight into the social changes that occur in the digital era. Keywords: digital era, social interaction, digital techniques